Accessory Proteins of the Nitrogenase Assembly, NifW, NifX/NafY, and NifZ, Are Essential for Diazotrophic Growth in the Nonheterocystous Cyanobacterium Leptolyngbya boryana - Nonaka, Aoi; Yamamoto, Haruki; Kamiya, Narumi; Kotani, Hiroya; Yamakawa, Hisanori; Tsujimoto, Ryoma; Fujita, Yuichi (Frontiers in Microbiology, 2019)
Since nitrogenase is extremely vulnerable to oxygen, aerobic or micro-aerobic nitrogen-fixing organisms need to create anaerobic microenvironments in the cells for diazotrophic growth, which would be one of the major barriers to express active nitrogenase in plants in efforts to create nitrogen-fixing plants. Numerous cyanobacteria are able to fix nitrogen with nitrogenase by coping with the endogenous oxygen production by photosynthesis. Understanding of the molecular mechanisms enabling to the coexistence of nitrogen fixation and photosynthesis in nonheterocystous cyanobacteria could offer valuable insights for the transfer of nitrogen fixation capacity into plants. We previously identified the cnfR gene encoding the master regulator for the nitrogen fixation (nif) gene cluster in the genome of a nonheterocystous cyanobacterium Leptolyngbya boryana, in addition to initial characterization of the nif gene cluster. Here we isolated nine mutants, in which the nif and nif-related genes were individually knocked out in L. boryana to investigate the individual functions of (1) accessory proteins (NifW, NifX/NafY, and NifZ) in the biosynthesis of nitrogenase metallocenters, (2) serine acetyltransferase (NifP) in cysteine supply for iron-sulfur clusters, (3) pyruvate formate lyase in anaerobic metabolism, and (4) NifT and HesAB proteins. ΔnifW, ΔnifXnafY, and ΔnifZ exhibited the most severe phenotype characterized by low nitrogenase activity (<10%) and loss of diazotrophic growth ability. The phenotypes of ΔnifX, ΔnafY, and ΔnifXnafY suggested that the functions of the homologous proteins NifX and NafY partially overlap. ΔnifP exhibited significantly slower diazotrophic growth than the wild type, with lower nitrogenase activity (22%). The other four mutants (ΔpflB, ΔnifT, ΔhesA, and ΔhesB) grew diazotrophically similar to the wild type. Western blot analysis revealed a high correlation between nitrogenase activity and NifD contents, suggesting that NifD is more susceptible to proteolytic degradation than NifK in L. boryana. The phenotype of the mutants lacking the accessory proteins was more severe than that observed in heterotrophic bacteria such as Azotobacter vinelandii, which suggests that the functions of NifW, NifX/NafY, and NifZ are critical for diazotrophic growth of oxygenic photosynthetic cells. L. boryana provides a promising model for studying the molecular mechanisms that produce active nitrogenase, to facilitate the creation of nitrogen-fixing plants.